Integrating Tri Hita Karana into Entrepreneurial Orientation for Business Sustainability in Balinese MSMEs - Ni Wayan Sitiari; Made Setini; Anik Puspa Ningsih; Cokorda Krisna Yuda (AIBPM Publisher, 2026)
Business sustainability often varies depending on cultural perspectives. This study aims to explore business sustainability through the lens of entrepreneurial orientation practices, specifically from the Tri Hita Karana (THK) cultural perspective in Bali. The research employs a qualitative approach, with respondents including owners and managers of Micro, Small, and Medium Enterprises (MSMEs), community leaders, and academics from Bali. The findings of the study reveal that business sustainability, as seen through the THK cultural perspective in Bali, encompasses entrepreneurial orientation practices such as maintaining a harmonious relationship with God by seeking taksu, fostering harmonious relationships with others through memyamabraya, and protecting the natural environment and its resources by safeguarding the earth. Business sustainability, viewed through the lens of cultural values, can help maintain long-term business viability in Bali; however, it tends not to promote growth at the scale of larger companies. The findings of this study indicate that MSMEs in Bali, with a deep understanding of their culture, tend to preserve traditional business practices, which, while sustainable, often hinder the transition to larger-scale enterprises. The results provide insights for policymakers in designing culturally grounded strategies to enhance both the sustainability and growth potential of MSMEs.